The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0071392
|View full text |Cite
|
Sign up to set email alerts
|

Diethylhexyl Phthalates Is Associated with Insulin Resistance via Oxidative Stress in the Elderly: A Panel Study

Abstract: BackgroundInsulin resistance (IR) is believed to be the underlying mechanism of metabolic syndrome and type 2 diabetes mellitus (DM). Recently, a few studies have demonstrated that phthalates could cause oxidative stress which would contribute to the development of IR. Therefore, we evaluated whether exposure to phthalates affects IR, and oxidative stress is involved in the phthalates-IR pathway.MethodsWe recruited 560 elderly participants, and obtained blood and urine samples during repeated medical examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 56 publications
5
72
1
Order By: Relevance
“…Geometric means of MEOHP, MEHHP, and MnBP at enrollment were 15.48 μg/L, 21.11 μg/L, and 28.23 μg/L, respectively (see Additional file 1: Table S2), which are comparable to previously reported levels in the Republic of Korea [6, 7], but higher than those in the United States [26]. The levels of each phthalate metabolite were correlated at multiple time points (see Additional file 1: Table S3).…”
Section: Resultssupporting
confidence: 84%
“…Geometric means of MEOHP, MEHHP, and MnBP at enrollment were 15.48 μg/L, 21.11 μg/L, and 28.23 μg/L, respectively (see Additional file 1: Table S2), which are comparable to previously reported levels in the Republic of Korea [6, 7], but higher than those in the United States [26]. The levels of each phthalate metabolite were correlated at multiple time points (see Additional file 1: Table S3).…”
Section: Resultssupporting
confidence: 84%
“…Previously, positive relationships were found between biomarkers of oxidative stress, including 8-isoprostane, malondialdehyde (MDA) and 8-oxo-2 1 -deoxyguanosine (8-oxo-dG), with phthalate metabolite concentrations [4,26,32,75]. In our cohort, at 13 weeks of pregnancy, only two HMW metabolites (MCOP and MCNP) were significantly associated with 8-isoprostane.…”
Section: Discussionmentioning
confidence: 51%
“…DDE) as well as various PCB congeners, positively associate with obesity, abdominal adiposity, and components of the metabolic syndrome [15,27,28,29]. Phthalates are used in the plastics industry as well as in various consumer goods and medical devices [30], and phthalate metabolites have been associated with insulin resistance and abdominal obesity [31,32]. Insulin resistance has also been shown to correlate with urinary concentrations of BPA [33] and serum dioxin levels [34].…”
Section: Epidemiological Studies Linking Edcs With Diabetes and Cardimentioning
confidence: 99%
“…A recent epidemiological study showed that urinary phthalate (e.g. DEHP) levels correlated with levels of the oxidative stress marker malondialdehyde [32], further suggesting this mechanism as relevant for EDC-mediated atherosclerotic disease. Uptake of oxidized LDL by endothelial cells has been shown to be up-regulated by arsenic [139]; whether arsenic has similar effects in promoting macrophage foam cell formation, however, requires further study.…”
Section: Mechanisms Of Edc-induced Metabolic Dysregulation and Cardiomentioning
confidence: 99%